Neurodevelopmental disorders. Issue 1 (1st December 2016) - D'Souza, Hana; Karmiloff‐Smith, Annette
Abstract : Recent technological advances allow us to measure how the infant brain functions in ways that were not possible just a decade ago. Although methodological advances are exciting, we must also consider how theories guide research: what we look for and how we explain what we find. Indeed, the ways in which research findings are interpreted affects the design of policies, educational practices, and interventions. Thus, the theoretical approaches adopted by scientists have a real impact on the lives of children with neurodevelopmental disorders (NDDs) and their families, as well as on the wider community. Here, we introduce and compare two theoretical approaches that are used to understand NDDs: the neuropsychological account and neuroconstructivism . We show how the former, adult account, is inadequate for explaining NDDs and illustrate this using the examples of Williams syndrome and specific language impairment. Neuroconstructivism, by contrast, focuses on the developing organism and is helping to change the way in which NDDs are investigated. Whereas neuropsychological static approaches assume that one or more 'modules' (e.g., visuospatial ability in Williams syndrome) are impaired while the rest of the system is spared (e.g., language in Williams syndrome), neuroconstructivism proposes that basic‐level deficits have subtle cascading effects on numerous domains over development. Neuroconstructivism leads researchers to embrace complexity by establishing large research consortia to integrate findings at multiple levels (e.g., genetic, neural, cognitive, environmental) across developmental time. WIREs Cogn Sci 2017, 8:e1398. doi: 10.1002/wcs.1398 This article is categorized under: Neuroscience > Development